(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In our day-to-day lives, the internet is quite crucial. We utilize the internet virtually every day for almost all of our tasks. Buying and selling used to be done in the marketplaces without the internet, but with the emergence of e-commerce in India, our lives have become more easy due to its many benefits. Online shopping is a kind of e-commerce that is mostly carried out by users thanks to e-commerce websites in India that enable us to purchase and sell things of our choosing at a reasonable price. E-commerce websites have a wide range of effects on various marketplaces and merchants. We shall cover the various marketplaces and merchants, as well as the effects of e-commerce on them, in this article.